Teacher's Perception and Role of Learning for Children with Special Needs - Novia Solichah; Rifa Hidayah (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2021)
Children with special needs (ABK) are children who have special characteristics and are different from children as usual, in other words they are not able to show mental, emotional or physical disabilities, which are included in the category of children with special needs including: blind, deaf, mentally retarded, physically disabled, mentally retarded, learning difficulties, and behavioral difficulties. Barriers to the education of children with special needs require the form of educational services that are in accordance with their abilities and potential. The purpose of this study was to examine the description of the perception and role of teachers on the learning of children with special needs. This research method uses descriptive qualitative. This research was conducted in Malang City. The result of this study is that in general, teachers perceive children with special needs as requiring intensive learning. Children with special needs need continuous guidance between teachers and parents. This can be started with home visit activities or home visits. In order to improve the readiness of classroom teachers in dealing with children with special needs and provide a shadow teacher to facilitate children with special needs. The teacher as a teacher in his role also focuses on training the independence of children because children with special needs cannot always depend on others but at least children with special needs can take care of themselves.